O contrato de comunicação nos classificados sexuais: estratégias discursivas de legitimação do enunciador - Costa, Wagner Alexandre dos Santos (2007)
It´s intended this text, analysing especially by the angle which shows quality (the classifieds about prostitutes) called sexual classifieds, published in periodicals of Rio de Janeiro. In these classifieds, we will do a survey of the set of linguistic estrategies used by the speaker in the building of its image to the adressee. In the current research we will make the analysis of the social and linguistic diagram(Charaudeau, 1996) also, the conditions of legitimacy and credibility which reinforce the use of such estrategie. Concluding, we will search for the profile of the speaker, by grouping it in categories which are socials and economics, according to pieces of information gathered in the advertisiment